Materi Ajar Digital Berbasis Kearifan Lokal Pada Topik Sumber Energi Panas Untuk Kelas V Sekolah Dasar - Ni Made Dina Rahmawati; I Gede Margunayasa (Universitas Pendidikan Ganesha, 2022)
The COVID-19 pandemic has led to the implementation of online learning activities. Online learning activities have not run optimally due to the lack of teaching materials and digital skills possessed by teachers. This study aims to create android-based local wisdom digital teaching materials on the topic of heat energy sources for fifth grade elementary school. The development model used in this study is the ADDIE model. The test subjects consisted of 1 material expert, 1 media expert, 2 teachers and 12 students. There are two data in this study, namely qualitative data and quantitative data. Data collection techniques using a questionnaire technique. The data collected was then analyzed descriptively quantitatively. The validity of android-based local wisdom digital teaching materials from material experts with a percentage of 96.5% and from media experts getting 96.5% in the very good category. The results of the practicality of android-based local wisdom digital teaching materials based on teacher assessments obtained 99.4% and the percentage of students' practicality tests 98.7%. The results showed that the local wisdom digital teaching materials based on Android on the topic of heat energy sources for grade V elementary school were valid and practical to use. The implications of this research are expected to help students understand learning materials during online learning.